Numerical groundwater flow modeling of the northern river catchment of the Lake Tana, Upper Blue Basin, Ethiopia - Asrie, Nigussie Ayehu; Sebhat, Mesenbet Yibeltal (Journal of Agriculture and Environment for International Development (JAEID), 2016)
The study area is found North Western plateau in the North Gondar zone, Amhara regional state, Ethiopia. Its total surface coverage is 1887km2.The study area boundary was delineated from 90m Shutter Radar Terrain Mapping (SRTM) digital elevation model (DEM) using Global Mapper 8 software. Based on geologic information of the study area, unconfined subsurface flow condition was considered and simulated using MODFLOW 2000. The model calibration accounts the matching of the 58 observation point with simulated head with a permissible residual head of ±10m. 75% of the difference the observed and measured water level head in the study area is 5m. . The model was calibrated with mean error 0.506, absolute mean error 4.431m and standard deviation 6.083m. Based on the calibration process, the model is very sensitive in decreasing order change in recharge, hydraulic conductivity, and stream bed conductance. The simulated out flow of the model is 205.7Mm3/year which is nearly equal to simulated inflow with difference 2,887.45m3/yr. The base flow simulated discharge Megech River holds 35.8% of the out flow. The river contributed as recharge in to the aquifer that accounts to 15.3% of the inflow. Steady state withdrawal rates were increased by 15%, 35%, 55%, 75% and 100% to study the response of the system in this scenario. From the simulation results, one can observe that the development of a new groundwater sources would not pose appreciable impact in case of 15% and 35% withdrawal the head declines in this case is insignificant relative to the steady state withdrawal rate and the natural discharges were not altered highly. The simulation result indicated that the stream leakage decreased by 7.9% relative to the whole steady state value, but showed 14.9% decrease for Angereb, Keha, and Shinta river segments near the well field area. The water tables decline by 3.6m to18.8m in head observation in the well field area. The steady state simulated recharge was decreased by 32% and the simulation results showed on average head decrease of 8.06m over the whole area; with the highest fall 32m in wells to north and a minimum of about 1m in wells to the south of the catchment. In addition, the stream leakage, compared to the simulated steady state value and it was decreased by 75.36%. The simulated value showed an average 2.74m increased head over the whole area. High difference values were observed at Tseda (7.83m) and Koladiba (7.3m). The minimum difference 1.08m was recorded at Angereb well field (observation 94). In addition, the stream leakage compared with the steady state value the change was about 87.43%. Keywords: MODFLOW 2000, Groundwater, Modelling, Sensitivity analysis, Simulation, Recharge